Correlational study of the motivational climate in relation to physical-health variables in physical education teachers in training - Melguizo-Ibáñez, Eduardo; Alonso-Vargas, José Manuel; Ubago-Jiménez, José Luis; Sanz-Martín, Daniel; Puertas-Molero, Pilar (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Currently, the study of motivation within the physical sports environment is a subject that has been widely studied, as well as the physical-healthy variables in the young population. For this reason, the present research aims to study the relationships between motivational climate, physical activity practice and adherence to the Mediterranean diet in physical education teachers in training. For this purpose, a descriptive cross-sectional study was carried out in a sample composed of a total of 558 participants (M=21.37±0.35). An ad hoc questionnaire, the Perceived Motivational Climate in Sport Questionnaire-2 (PMCSQ-2) and the PREDIMED questionnaire were used for data collection. The data reveal that task climate and ego climate are positively correlated with the practice of physical activity; however, it is observed that the motivational climate plays a key role in achieving a positive adherence to a healthy dietary pattern.